Education is a private matter: Clinical midwives' experiences of being part-time master's students in midwifery. (August 2019) - Dahl, Bente; Røseth, Idun; Lyberg, Anne; Bongaardt, Rob; Sommerseth, Eva
Abstract: When the master's degree in midwifery was introduced in Norway, clinical midwives with a professional diploma soon requested the possibility to upgrade their education to a master's degree. In 2014, a part-time master's program worth 40 ECTS credits was introduced at a Norwegian university. In this study, we aimed to explore clinical midwives' experiences of how taking a part-time master's program in midwifery was received at their workplace. We employed a qualitative research design and an explorative descriptive approach. A convenience sample consisting of 47 clinical midwifes with varying seniority was recruited in 2016 and 2017, and five focus group interviews were conducted at the end of the study programs. Systematic text condensation was used to analyze the data, generating three themes. The first concerns the midwives' experiences of learning new tools to advance their profession. Secondly, they expressed hope for support, but found that education was a private matter. Finally, they experienced that financial support depended on goodwill from their employers. The study demonstrates that a master's degree in midwifery can be instrumental to strengthen clinical practice, but also points towards the need to update and strengthen management and leadership to facilitate and implement new knowledge. Highlights: The midwives learned new tools to advance their profession. The midwives found that further education was a private matter. Crossing the lines of professional conduct came at a private cost.